2016
DOI: 10.1089/lap.2016.0085
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Achalasia by Pediatric Surgeons: A Survey of the International Pediatric Endosurgical Group

Abstract: Given the infrequency of achalasia in children, there are a range of treatment plans among pediatric surgeons. We have identified current practices as a first step in developing more standard treatment pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Esophageal manometry was available in most centers but was only considered by half to be the most important diagnostic investigation. These findings are consistent with a survey conducted by the International Pediatric Endosurgical group, where 73% requested a manometry before intervention (14). Access to and experience with HRM remains a limitation in pediatric practice despite the fact that HRM is now considered the best test for diagnosing and subtyping achalasia in adult patients.…”
Section: Discussionsupporting
confidence: 90%
“…Esophageal manometry was available in most centers but was only considered by half to be the most important diagnostic investigation. These findings are consistent with a survey conducted by the International Pediatric Endosurgical group, where 73% requested a manometry before intervention (14). Access to and experience with HRM remains a limitation in pediatric practice despite the fact that HRM is now considered the best test for diagnosing and subtyping achalasia in adult patients.…”
Section: Discussionsupporting
confidence: 90%
“…[23] The current lack of evidence supporting one treatment approach over another, combined with the rarity of achalasia in children, has led to wide variation in practice. [24] Well-designed multi-institutional studies are needed to improve treatment and prevent the adverse impact this disease has on a child's long-term quality of life. [16]…”
Section: Esophageal Achalasiamentioning
confidence: 99%
“…LHM for achalasia was first described in 1991 by Shimi et al 28 It was later introduced as a treatment for children by Holcomb et al 29 Since then, many authors have demonstrated that LHM is a safe and effective treatment even in pediatric age. [30][31][32][33][34] A recent survey among International Pediatric Endosurgical Group members outlined LHM as preferred technique in the treatment of pediatric EA. Results were consistent across the patient ages, and 94% of responders performed a concomitant partial gastric fundoplication.…”
Section: Discussionmentioning
confidence: 99%